RAGAM TINDAK TUTUR ILOKUSI PADA NOVEL TERJEMAHAN THE DAVINCI CODE KARYA DAN BROWN - Suci Khaofia (Center of Language and Cultural Studies, 2017)
This research examined how illocutionary acts were applied in Dan Brown’s novel “The Da Vinci Code”. The dialogues of character which had illocutionary acts were used as the data of this research. The researcher then analyzed the data by applying qualitative analysis approach. The finding showed 20 kinds and five different patterns of illocutionary act were identified. The patterns included: (1) illocutionary act of directive “ask” used by participants who have the distance and power; (2) illocutionary act of directive “command” used by participants who have distance and power; (3) illocutionary act of assertive “allege” used by participants who have no distance but power and directive “ask” used by participants who has no distance nor power; (4) direct “command” used by participants who have no distance but power; and (5) direct illocutionary act mostly used by participants who have power and distance and participants who has no distance nor power.